Concentration and Distribution of Attention in Sports Swimming, Competitive and Rhythmic Gymnastics - Volodymyr Davydov; Anna Mankevych; Lushchyk Iryna (Lesya Ukrainka Volyn National University, 2016)
Swimming in conditions of training and competition is considered as a specific sports activity that creates conditions for the appearance and development of diverse mental features of a person, including for such property as attention. In our work attention is considered as one of the properties of an individual athlete which ensures the implementation of its sports activity, it is one of the mechanisms of its control and regulation. Tasks of the work are to assess the level of concentration and distribution of attention among swimmers and gymnasts, and to compare the obtained data from athletes with different levels of mastery and the same level of mastery. It is shown that with the growth of sports mastery of swimmers there is the tendency of growth of quantitative indicators of concentration and distribution of attention. It was found out that the role of attention as a mechanism of control and regulation of activity varies in different kinds of sports activities. In gymnastics (competitive and rhythmic) concentration of attention and especially its stability play a more prominent role than in swimming.